Biological performance of Menochilus sexmaculatus Fabricius (Coleoptera Coccinellidae) upon exposure to sublethal concentration of Imidacloprid - Yusof Ibrahim, Kueh T.F., (N/A, 2013)
Biological performance of Menochilus sexmaculatus Fabricius (Coleoptera Coccinellidae) upon exposure to sublethal concentration of Imidacloprid by Yusof Ibrahim, Kueh T.F.,